Impact of multi-drug resistance on clinical outcomes of dogs with corneal ulcers infected with Staphylococcus pseudintermedius - Mauer, Ashley N.; Allbaugh, Rachel A.; Kreuder, Amanda J.; Sebbag, Lionel (Frontiers in Veterinary Science, 2022)
Objective: Compare characteristics and clinical outcomes of dogs with infectious keratitis from Staphylococcus pseudintermedius considered to be multidrug-resistant (MDR) or not. Procedures: Staphylococcus pseudintermedius isolated as the primary pathogen from canine patients with ulcerative keratitis were considered MDR if resistant to at least one agent in three or more classes of antibiotics. Medical records were reviewed for history, patients’ characteristics, clinical appearance, therapeutic interventions, and clinical outcomes. Results: Twenty-eight dogs (28 eyes) were included. Compared to non-MDR cases, MDR diagnosis was significantly more common in dogs with recent (≤ 30 days) anesthesia (7/15 vs. 1/13, P=0.038) and more common in non-brachycephalic dogs (8/15 vs. 2/13, P=0.055). Clinical appearance (ulcer size/depth, anterior chamber reaction, etc.) did not differ significantly between groups (P≥0.055). Median (range) time to re-epithelialization was longer in MDR vs. non-MDR eyes [29(10-47) vs. 22(7-42) days] but the difference was not significant (P=0.301). Follow-up time was significantly longer in dogs with MDR keratitis [47(29-590) vs. 29(13-148) days, P=0.009). No other significant differences were noted between MDR and non-MDR eyes in regard to time for ulcer stabilization [4(1-17) days vs. 4(1-12), P=0.699], number of eyes requiring surgical stabilization (7/15 vs. 7/13, P=0.246) or enucleation (1/15 vs. 2/13, P=1.000), success in maintaining globe (14/15 vs. 11/13, P=0.583) or success in maintaining vision (12/15 vs. 10/13, P=1.000). Conclusions: MDR infections may prolong corneal healing time but did not appear to affect overall clinical outcomes in dogs with bacterial keratitis. Further research is warranted in a larger canine population and other bacterial species.